Green microwave-assisted combustion synthesis of Zinc oxide nanoparticles with Citrullus colocynthis (L.) Schrad: characterization and biomedical applications - Azizi, Susan; Mohamad, Rosfarizan; Shahri, Mahnaz Mahdavi (MDPI, 2017)
In this paper, a green microwave-assisted combustion approach to synthesize ZnO-NPs using zinc nitrate and Citrullus colocynthis (L.) Schrad (fruit, seed and pulp) extracts as bio-fuels is reported. The structure, optical, and colloidal properties of the synthesized ZnO-NP samples were studied. Results illustrate that the morphology and particle size of the ZnO samples are different and depend on the bio-fuel. The XRD results revealed that hexagonal wurtzite ZnO-NPs with mean particle size of 27–85 nm were produced by different bio-fuels. The optical band gap was increased from 3.25 to 3.40 eV with the decreasing of particle size. FTIR results showed some differences in the surface structures of the as-synthesized ZnO-NP samples. This led to differences in the zeta potential, hydrodynamic size, and more significantly, antioxidant activity through scavenging of 1, 1-Diphenyl-2-picrylhydrazyl (DPPH) free radicals. In in vitro cytotoxicity studies on 3T3 cells, a dose dependent toxicity with non-toxic effect of concentration below 0.26 mg/mL was shown for ZnO-NP samples. Furthermore, the as-synthesized ZnO-NPs inhibited the growth of medically significant pathogenic gram-positive (Bacillus subtilis and Methicillin-resistant Staphylococcus aurous) and gram-negative (Peseudomonas aeruginosa and Escherichia coli) bacteria. This study provides a simple, green and efficient approach to produce ZnO nanoparticles for various applications.